2017
DOI: 10.14254/2071-8330.2017/10-2/9
|View full text |Cite
|
Sign up to set email alerts
|

Leading factors in the formation of innovative education environment

Abstract: Abstract. The article considers the problem of forming innovative education environment at the universities along with the problem of ensuring long-term competitiveness of education services at both national and global markets. The management model of an innovative education environment is offered, with particular attention being paid to the development of innovative technologies of global education as well as education services' export. Based on the statistical study of the dynamics in the number and composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 18 publications
0
11
0
3
Order By: Relevance
“…Step 1, which consisted of preparation for learning management (P), is validated by research from Thaiposri and Wannapiroon (2015), which indicated that in use of social media and ICT in teaching critical thinking skills, preparation was highly important, with teaching staff forming the core of an innovative educational environment (Gulicheva et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Step 1, which consisted of preparation for learning management (P), is validated by research from Thaiposri and Wannapiroon (2015), which indicated that in use of social media and ICT in teaching critical thinking skills, preparation was highly important, with teaching staff forming the core of an innovative educational environment (Gulicheva et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Input from the study's nine experts who reviewed the model and from suggestions from other model developers, led to the selection of easy to remember letters that describe each step's process. (Gulicheva, Lisin, Osipova, & Khabdullin 2017;Paul et al, 1997;Thaiposri & Wannapiroon, 2015;Wichadee, 2014;Schroeder, Minocha, & Schneider, 2010). U -Step 2 Understanding and practice Dewey, 1910;Halpern, 1993;Hove, 2011;McPeck, 1981; University of Leeds, n/d).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Industrial Revolution 4.0 provides the advent of the digital age, and claims that educational institutions embrace an education revolution too. Education 4.0 provides the notion of teaching and learning innovation and uses information and technology in its processes (Gulicheva et al 2017;Anggraeni 2018). As well as educational institutions individuals are considering adopting Education 4.0.…”
Section: Introductionmentioning
confidence: 99%
“…Социально-трудовые отношения представляют собой сложную систему многоуровневых общественных отношений, существующих между наемными работниками, работодателями и государством в процессе трудовой деятельности, нацеленную на обеспечение необходимого уровня и качества жизни человека, трудового коллектива и общества, системное представление которых позволяет выделить в их структуре взаимосвязанные экономические и социальные элементы (Rakovskaya et al, 2012;Janda et al, 2013;Kachura, 2015;Gulicheva et al, 2017;Mikhaylov, 2018).…”
Section: проблематика воспроизводства человеческого капитала в высшейunclassified
“…При этом формирование системы социально-трудовых отношений предопределяется совокупностью разнообразных условий и факторов, классифицируемых по различным признакам: общие (политические, экономические, социальные, правовые); частные (стратегии развития, кадровый потенциал); специфические (кадровая политика, демографические факторы) (Farrell et al, 2005;Grozova & Tsvetkova, 2012;Simionescu et al, 2016).…”
Section: проблематика воспроизводства человеческого капитала в высшейunclassified